A randomized double blind comparative study of dexmedetomidine with midazolam for intranasal premedication in children undergoing ophtalmic surgery. - D. Singla; G. Chaudhry; J. Dureja; M. Mangla (Pediatric Anesthesia and Critical Care Journal (PACCJ))
Introduction Anxiety and pain are important and frequently encoun- tered issues in children especially during acute postope- rative period immediately after emergence from anae- sthesia. Additionally during ophthalmic surgical proce- dures, this is further compounded by inability to open one or both eyes post operatively. So, this study was planned to compare the efficacy of dexmedetomidine with midazolam used as intranasal premedication in children undergoing elective ophthalmic surgeries under general anaesthesia on post-operative analgesia, seda- tion and post-operative analgesic requirement. Materials and Methods 60 Children aged 3 to 10 years, American society of anaesthesia (ASA) class I or II posted for elective ophthalmic surgery under general anaesthesia were ran- domly allocated into two groups (group D and L). Chil- dren in-group D received Dexmedetomidine 1 μg/kg in- tranasally approximately 30 mins before the start of sur- gery. Children in-group M received intranasal midazo- lam 0.2 mg/kg approx. 30 mins before surgery. Results Children in group D had significantly lower values on objective pain scale when noted 1⁄2 hourly for first 2 hours post operatively. Likewise, Dexmedetomidine group has lower requirement of inj. Fentanyl. (07 doses in 06 children vs. 14 doses in 12 children) Conclusions Intra nasal dexmedetomidine premedication in children produced stable heart rate and systolic blood pressure during preoperative period and lowered the objective pain score with reduced analgesic requirement in post- operative period